Clinical pharmacology during pregnancy - Mattison, Donald R. (Academic Press is an imprint of Elsevier, 2013)
Clinical Pharmacology During Pregnancy is written for clinicians, physicians, midwives, nurses, pharmacists and other medical professionals directly involved in the care of women during pregnancy. This book focuses on the impact of pregnancy on drug disposition and also includes coverage of treatments for diseases of specific body systems, as well as essential content on dosing and efficacy. Written in a clear and practical manner, this reference provides easily accessible information and clinical guidance on how best to treat women with medications during pregnancy. Utilizes an evidence-based approach for therapeutics during pregnancy. Includes a summary of specific medications by indication with up-to-date information on dosing and efficacy in pregnancy for the given indication. Highlights current research in this area and provides easily accessible and vital information for clinicians Complements the companion volume, Drugs During Pregnancy and Lactation by Schaefer et al and presents a bundling opportunity to the same target audience of medical professionals. Includes a companion website containing support materials for professional or continuing education courses in OB pharmacology.